Sperm morphology and DNA fragmentation after zona pellucida selection - Rumiana Ganeva; Dimitar Parvanov; Denitsa Velikova; Magdalena Vasileva; Kristina Nikolova; Georgi Stamenov (Bioscientifica, 2021)
Sperm DNA fragmentation (SDF) and sperm morphological defects can negatively affect ART outcomes. Consequently, there is a need for additional semen processing technique that accounts for sperm DNA status and morphology prior to ICSI. The objective was to evaluate the efficacy of an additional zona pellucida adhesion-based sperm selection for obtaining sperm populations with a high percentage of normal morphology and DNA integrity as compared to native semen and routine swim-up preparation. Semen samples from 78 normozoospermic men were subjected to swim up and placed in petri dishes coated with 48 acid-solubilized zonae pellucidae. Sperm DNA fragmentation and morphology were assessed in the native semen, the swim-up samples, and the zona-adhered spermatozoa from each patient. The mean sperm DNA fragmentation of the zona-selected spermatozoa (3.5 ± 0.7%) was significantly lower than the swim-up samples (15.3 ± 5.2%) (P < 0.001) and native semen (24.9 ± 7.1%) (P < 0.001). All of the samples had lower levels of DNA damage after additional selection by zona pellucida adhesion. Significantly higher percentage of sperm with normal morphology was observed after zona-adhesion selection (11.4 ± 3.9%) when compared to the swim-up samples (8.9 ± 4.3%) (P < 0.001) or the native semen (5.3 ± 3.2%) (P < 0.001). In 94% of the samples, the percentage of spermatozoa with normal morphology increased after the additional zona selection. This study demonstrates that sperm selection by additional zona-adhesion technique yields a significantly higher percentage of spermatozoa with normal morphology as well as a significantly decreased level of DNA fragmentation when compared to the native semen and the swim-up-only prepared samples.